Effect of sealants in the composite surface roughness after tooth brushing (Bioscience Journal, 2014)
This in vitro study evaluated the influence of 4 surface sealers on the surface roughness of composite resins. Fifty specimens were divided into 10 groups, as follows: G1. (Control 1) Concept resin; G2. Concept + Fortify; G3. Concept + Biscover; G4. Concept + Lasting Touch; G5. Concept + Fill Glaze; G6. (Control 2) Esthet X; G7. Esthet X + Fortify; G8. Esthet X + Biscover; G9. Esthet X + Lasting Touch; G10. Esthet X + Fill Glaze. Specimens (15mm in length, 4 mm in depth and 5 mm in width) were made using a matrix and were stored in distilled water at 37ºC for 24 hours. After storage, specimens were polished using 320, 600 abrasive SiC paper under running water and the initial roughness was measured using a perfilometer. Surface sealers were applied and a new measurement of roughness was made. Specimens were submitted to 100,000 cycles of abrasive dentifrice brushing followed by another surface roughness measurement. Qualitative analysis was made by using SEM. Results were submitted to 3-way modified ANOVA (p